Policy narratives of circular economy in the EU – Assessing the embeddedness of water and land in national action plans. (15th March 2021) - Fidélis, Teresa; Cardoso, Andreia Saavedra; Riazi, Fayaz; Miranda, Ana Catarina; Abrantes, João; Teles, Filipe; Roebeling, Peter C.
Abstract: Following the challenges of the European Union (EU), member states have adopted circular economy (CE) plans and strategies, with objectives and measures to foster circularity. Although the concept of CE refers to various natural resources such as water and land, little is known on how current CE policies are integrating these environmental resources. This article assesses how water and land concerns are embedded in the EU CE action plans issued in 2015 and 2020 and a set of nine member states' subsequent national plans. The assessment used a content analysis based on two variables, the frequency of water and land' related terms and the consistency of their inclusion within the plans. The findings reveal that neither water nor land emerge as major concerns in the CE plans, in comparison to materials or waste. Also, they are not consistently associated with the typical components of the plans namely problem-showcase, objectives, strategies and measures, stakeholders, and CE performance indicators. Nevertheless, the embeddedness of water is more evident in the plans of southern countries, whereas land concerns are much more erratic. If water and land concerns, are to be at the forefront of the transition to circularity, as the literature recommends, and if these plans are expected to offer an integrated approach of the CE concept, further efforts should be made to ensure their embeddedness. Graphical abstract: Image 1 Highlights: Circular Economy is as complex and integrative concept. The narrative of circular economy action plans is screened by content analysis. Water and spatial concerns are peripheral concerns in CE action plans. Are not consistently associated with the typical components of an action plan. The transition into circularity requires stronger embeddedness of water and land.